Harnessing the Power of AI for Enhanced Diagnosis and Treatment of Hepatocellular Carcinoma - Jin, Ting; Luo, Mengchen; Chen, Feng; Bai, Jin; Ding, Jin (Turkish Journal of Gastroenterology, 2024)
Since its advent, artificial intelligence (AI) has been continuously researched, and substantial progress has been made in many fields,nsuch as the diagnosis and therapies for cancer. Due to the advantages of high efficiency, rapidity, and precision, AI has been increasingly adopted in the medical field to improve patient prognosis and the efficiency of medical procedures. Thus, AI technology has become a powerful driving force and support mechanism in the medical and health industry. Hepatocellular carcinoma (HCC) is the sixth most common cancer and the fourth leading cause of cancer mortality worldwide, with a 5-year relative survival rate of 18%. The early diag nosis and postsurgical treatment of HCC are key factors related to its prognosis, which provides an opportunity for the application of AI in HCC diagnosis and treatment. This review will summarize the application of AI in the diagnosis and treatment of HCC to provide prospects for deeper and wider applications. Cite this article as: Jin T, Luo M, Chen F, Bai J, Ding J. Harnessing the power of AI for enhanced diagnosis and treatment of hepatocellular carcinoma. Turk J Gastroenterol. 2025;36(4):200-208.